PENGEMBANGAN E-MODUL PEMBELAJARAN KIMIA PADA MATERI KOLOID BERBASIS KEARIFAN LOKAL PAPUA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Ardian Hangga Kelana; Sakka Irawan (Bajang Institute, 2024)
This research aims to find out how to create a chemistry e-module based on Papuan local wisdom, develop a chemistry e-module based on Papuan local wisdom, the feasibility of a chemistry e-module based on Papuan local wisdom, and improve student learning outcomes using chemistry e-modules based on local Papuan wisdom on colloidal materials. The research method used is Research and Development (R and D). This research was conducted in class XI IPA 1 of SMA YPK Diaspora Kotaraja Jayapura with a sample size of 30 students. The research results show that the chemistry e-module based on local Papuan wisdom on colloidal materials is very suitable for use as teaching material with an average validator assessment of 87%. The use of chemistry e-modules based on local Papuan wisdom can improve student learning outcomes with the n-Gain test obtaining an average of 0.55 in the medium category.